The Implementation of Strengthening Pancasila Student Profile’s (P5) Project at SDN Parsanga I - Armadi, Ali; Kumala, Rate Seftinindias Dwi (Universitas Trunojoyo Madura, 2023)
Strengthening the Pancasila Student Profile’s (P5) Project is one of the programs designed by the Ministry of Education and Culture that included in the independent curriculum. The main objective of implementing the P5 program is to create students with character and behavior in accordance with Pancasila. The approach used in P5 is project-based learning (PjBL). The purpose of this study is to describe the implementation of strengthening Pancasila student profile’s (P5) project at SDN Parsanga I that is one of the sekolah penggerak in Sumenep Regency, including the flow of implementation, the chosen of theme or topic, dimensions, elements, sub elements, and the target objectives of Pancasila Student Profile. The results of the study shows that each series of activities in the implementation of P5 is able to train students to develop the dimensions of Pancasila students in aspects of critical thinking and faith, piety to God Almighty and noble character. Students are involved in the activities that build a links between various information, analyze, evaluate and conclude information. In addition, contextualization activities occur so that students are able to link the theme of survival with the problem of waste in the surrounding environment so that it can bring out the behavior of protecting the environment as a form of morals towards nature.